Conjugated Linoleic Acid Production by Alkali Isomerization of Linoleic Acid from Idesia polycarpa Maxim. var. vestita Diels Oil - Wang, Q.Y.; Li, X.; Du, K.F.; Yao, S.; Song, H. (Asian Journal of Chemistry, 2013)
Increasing attention to conjugated linoleic acid for its significant biological effects attracted growing demand for conjugated linoleic acid related products. The isomerization of linoleic acid was regarded as a more promising option for large-scale production of conjugated linoleic acid. However, the availability of linoleic acid is a prerequisite for the technology. High purity linoleic acid from Idesia polycarpa Maxim. var. vestita Diels oil was used to synthesize conjugated linoleic acid in this work and response surface methodology was successfully employed to optimize the process. The optimal conditions for production of conjugated linoleic acid by alkaline isomerization were: a ratio of 1.0:0.4:5.2 (w/w/w) of linoleic acid/KOH/ethylene glycol, 188.3 ºC and 4.4 h. After the optimization process, the experimental purity of conjugated linoleic acid (89.72 %) corresponded to the predicted value. The high quality conjugated linoleic acid with a total yield of 30.84 % (w/w) from Idesia polycarpa Maxim. var. vestita Diels oil possesses a bright prospect as potential linoleic acid source for the production of conjugated linoleic acid.